Two decades of change in state, pressure and conservation responses in the coastal forest biodiversity hotspot of Tanzania. Issue 1 (11th March 2016) - Burgess, Neil D.; Malugu, Isaac; Sumbi, Peter; Kashindye, Almas; Kijazi, Adam; Tabor, Karyn; Mbilinyi, Boniface; Kashaigili, Japhet; Wright, Timothy Maxwell; Gereau, Roy E.; Coad, Lauren; Knights, Kathryn; et al.
Abstract: We present an analysis of changes of state, pressures and conservation responses over 20 years in the Tanzanian portion of the Coastal Forests of Eastern Africa biodiversity hotspot. Baseline data collected during 1989–1995 are compared with data from a synthesis of recently published papers and reports and new field work carried out across the region during 2010–2014. We show that biodiversity endemism values are largely unchanged, although two new species (amphibian and mammal) have been named and two extremely rare tree species have been relocated. However, forest habitat continues to be lost and degraded, largely as a result of agricultural expansion, charcoal production to supply cities with cooking fuel, logging for timber and cutting of wood for firewood and building poles. Habitat loss is linked to an increase in the number of species threatened over time. The government-managed forest reserve network has expanded slightly but has low effectiveness. Three forest reserves have been upgraded to National Parks and Nature Reserves, which have stricter protection and more effective enforcement. There has also been rapid development of village-owned forest reserves, with more than 140 now existing; although usually small, they are an important addition to the areas being managed for sustainable resource use, and also provide tangible benefits to local people. Human-use pressures remain intense in many areas, and combined with emerging pressures from mining, gas and oil exploration, many endemic species remain threatened with extinction.